2019
DOI: 10.1021/acs.jpcc.9b08187
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Ethanol and Water Adsorptions on Thermal Conductivity of ZIF-8

Abstract: Metal−organic frameworks are promising nanoporous materials for adsorption heat pumps (AHPs) using water and alcohols as working fluids due to their ultrahigh surface area. The heat transfer in porous crystals containing adsorbed gases is vital for their performance in adsorbed natural gas storage or AHPs. However, limited attention has been paid to their thermal properties. In this study, equilibrium molecular dynamics simulations were performed to investigate the impacts of ethanol/water adsorption on the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 35 publications
2
33
1
Order By: Relevance
“…The influence of guest molecules on the thermal conductivity of MOFs is still a topic of debate, but lies beyond the scope of the current study. 26,32,109,110 Some studies have suggested that guest molecules improve the heat transfer (i.e. the thermal conductivity increases with the loading), while others have reported the opposite.…”
Section: Thermal Conductivitymentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of guest molecules on the thermal conductivity of MOFs is still a topic of debate, but lies beyond the scope of the current study. 26,32,109,110 Some studies have suggested that guest molecules improve the heat transfer (i.e. the thermal conductivity increases with the loading), while others have reported the opposite.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…For practical MOF applications, the required amount of material will play an important role and is expected to remain constant throughout the operation of the device. Therefore, it is instructive to determine the absolute thermal conductivity κ abs , which is an extensive property (with units W/K): 30,110 with A the cross-sectional area perpendicular to the path of the heat flow (i-direction), d the thickness along the path of the heat flow, and κ the thermal conductivity along the path of the heat flow ( Figure S5). This quantity can be used to compare the heat transfer characteristics of the lp and the np phases for the same amount of matter, correcting for their different physical dimensions.…”
Section: Specific Vs Absolute Thermal Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…To data, only the thermal conductivity of some conventional SPCs such as MOF-5, [23][24][25][26] ZIF-8, [27][28][29][30][31][32] and HKUST-1 21,33,34 has been investigated in detail by experimental or computational approaches, while the thermal transport properties of the aforementioned DUT series remain unknown. In addition, the existing studies mainly focus on the influence of gas and water adsorption, 29,34 framework architecture, 24,28,[35][36][37] defects, 33 and physical environment including pressure 18 and temperature 20 on the thermal conductivity of SPCs, little attention has been paid to the evolution of the thermal transport properties of SPCs during their dynamic process, i.e., the phase transition. To the best of our knowledge, there are only two studies regarding the effect of phase transition on the thermal transport in SPCs using MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared with the gas adsorption property, the study of thermal transport in SPCs is still in its very early stage. To data, only the thermal conductivity of some conventional SPCs such as MOF-5, 23-26 ZIF-8, [27][28][29][30][31][32] and HKUST-1 21, 33,34 has been investigated in detail by experimental or computational approaches, while the thermal transport properties of the aforementioned DUT series still remain unknown. In addition, the existing studies mainly focus on the influence of gas and water adsorption, 29,34 framework architecture, 24,28,[35][36][37][38] defects, 33 and physical environment including pressure 18 and temperature 20 on the thermal conductivity of SPCs, little attention has been paid to the evolution of the thermal transport properties of SPCs during their dynamic process, i.e., the phase transition.…”
Section: Introductionmentioning
confidence: 99%